An agile standardized work procedure for cleaning the operating room - David Claudio; Virginia Cosgriff; Valentina Nino; Leonardo Valladares (Journal of Industrial Engineering and Management (JIEM), 2021)
Purpose: This research aimed to reduce the turnover time (non-operative time) in the operating room (OR) at a US Northwestern hospital.~Design/methodology/approach: Data collection consisted of observation and interviews of the aides, circulating nurses, and surgical techs to identify causes of delays and long turnovers. It was determined that the turnover could be divided into two stages: cleaning the room and setting up for the next surgery. The research team met with the staff (aides) to create a standard operating procedure for the cleaning stage. It was decided to create an agile standard procedure that would allow the process to be completed the same way effectively with any number of people ranging from 1 to 3. The flexibility accounts for the number of people who are to complete the procedure and considers that some of them are only available during portions of the cleaning stage due to multiple turnovers or duties. Findings:~The agile cleaning procedure reduced the cleaning time by 2.2 minutes (15.7% of the total time) and the standard deviation by 3.30 minutes. A decrease in variability represents more consistent turnovers, creating more predictable times for scheduling surgeries in the future. Originality/value: This research proposes a novel approach to standardized work that quickly adapts to the number of workers available. The agile standardized work procedure (ASWP) allows the process to be completed the same way every time effectively with any number of people.
Keywords: 650; agile; agile standardized work procedure; lean healthcare; Operating room; turnover